3D Temporary‐Magnetized Soft Robotic Structures for Enhanced Energy Harvesting. Issue 40 (15th August 2021) - Miao, Liming; Song, Yu; Ren, Zhongyang; Xu, Chen; Wan, Ji; Wang, Haobin; Guo, Hang; Xiang, Zehua; Han, Mengdi; Zhang, Haixia
Abstract: The advent of functional materials offers tremendous potential in a broad variety of areas such as electronics, robotics, and energy devices. Magnetic materials are an attractive candidate that enable multifunctional devices with capabilities in both sensing and actuation. However, current magnetic devices, especially those with complex motion modalities, rely on permanently magnetized materials with complicated, non‐uniform magnetization profiles. Here, based on magnetic materials with temporary‐magnetization, a mechanically guided assembly process successfully converts laser‐patterned 2D magnetic materials into judiciously engineered 3D structures, with dimensions and geometries ranging from mesoscale 3D filaments, to arrayed centimeter‐scale 3D membranes. With tailorable mechanical properties and highly adjustable geometries, 3D soft structures can exhibit various tethered locomotions under the precise control of magnetic fields, including local deformation, unidirectional tilting, and omnidirectional rotation, and can serve as dynamic surfaces for further integration with other functional materials or devices. Examples demonstrated here focus on energy‐harvesting systems, including 3D piezoelectric devices for noncontact conversion of mechanical energy and active motion sensing, as well as 3D solar tracking systems. The design strategy and resulting magnetic‐controlled 3D soft structures hold great promise not only for enhanced energy harvesting, but also for multimodal sensing, robotic interfaces, and biomedical devices. Abstract : Through a mechanically guided, compressive‐buckling process, a set of judiciously engineered 3D soft robotic structures can be developed based on magnetic materials. Under the precise control of the external magnetic‐field, the temporary‐magnetized 3D structures can achieve various tethered locomotion. Further integration with functional devices (piezoelectric energy harvester, solar cell) allows for enhanced energy harvesting, and potentially multimodal sensing and robotic interfaces.